Validation of the Spanish version of the Childhood Executive Functioning Inventory (CHEXI) in 4-5 year-old children - Giménez de la Peña, Almudena; López-Zamora, Miguel; Vila, Oscar; Sánchez, Auxiliadora; Thorell, Lisa B. (Anales de Psicología / Annals of Psychology, 2022)
Background: The Childhood Executive Functioning Inventory (CHEXI) was designed to identify EF deficits in daily life contexts. The aim of the present study was to validate the Spanish version of the CHEXI in 4-5-year-old children. Method: Parents’ ratings of the CHEXI and laboratory tests of EF were investigated in two large samples of 445 children aged 4 years (196 girls, 249 boys) and 459 children aged 5 years (208 girls, 251 boys). CHEXI ratings were collected again after one-year. Results: The two-factor structure of the CHEXI (i.e., Working Memory and Inhibition) was replicated, showing high internal consistency and temporal stability. The 4-year-olds were reported to have higher EF deficits than 5-year-olds have. Boys were rated as having higher EF deficits than girls were. However, gender differences were not significant contrasting performance on EF tasks. Finally, associations between CHEXI ratings and EF tests were weak, suggesting that EF tests and EF ratings capture different aspects of EF. Conclusions: The Spanish CHEXI provides a suitable instrument to assess EF in 4-5-year-old children.